Multiple primary melanomas: do they look the same?. (5th June 2013) - Moscarella, E.; Rabinovitz, H.; Puig, S.; Zalaudek, I.; Oliviero, M.C.; Brown, L.; Alarcon, I.; Malvehy, J.; Longo, C.; Formisano, D.; Carrera, C.; Badenas, C.; et al.
Summary Background A series of studies has investigated epidemiological, clinical and genetic characteristics of patients with multiple primary melanoma (MPM). However, comparison of the clinical and dermoscopic features of MPM within a given individual has been described only in case reports. Objectives To describe the dermoscopic features of MPM for each given patient, and to evaluate the characteristics eventually associated with similar or dissimilar appearance. Methods From the databases of three skin‐lesion clinics in the U.S.A., Italy and Spain we collected the dermoscopic images of melanomas in patients diagnosed with MPM. Results Among 58 patients with MPM, we found that 53% of patients had dermoscopically similar melanomas and 47% of patients had dermoscopically different melanomas. In older patients 59% of melanomas were dermoscopically similar vs. 47% in younger patients (P = 0·377). Similar thickness was associated with the occurrence of dermoscopically similar melanomas (19/30 cases, 63%; P = 0·039). Most (65%) of the synchronous lesions were similar, compared with 36% of nonsynchronous lesions (P = 0·029), and most (69%) of the melanomas on sun‐damaged skin were similar, vs. 37% of melanomas on nonsun‐damaged skin (P = 0·015; odds ratio 3·88, 95% confidence interval 1·11–13·98). The percentage of dermoscopically different melanomas was higher in patients with a family history of melanoma (67% vs. 48%). Conclusions MPMs in a given patient have almost the same chance of looking dermoscopically similar or different. However, a subset of elderly patients with sun‐damaged skin may present multiple, similar, thin melanomas characterized by pigment‐network and regression structures.